Long-Term Impact of Immunosuppressants at Therapeutic Doses on Male Reproductive System in Unilateral Nephrectomized Rats: A Comparative Study. (11th July 2013) - Chen, Yehui; Zhang, Zhi; Lin, Yun; Lin, Huaxin; Li, Miaoyuan; Nie, Pin; Chen, Lizhong; Qiu, Jiang; Lu, Yanmeng; Chen, Linqiang; Xu, Banglao; Lin, Wuzhou; et al.
Abstract : Cyclosporine, tacrolimus, and sirolimus are commonly used in renal transplant recipients to prevent rejection. However, information for comparative effects of these agents on the male productive system is extremely limited and controversial. In a physiologically and clinically relevant rat model of unilateral nephrectomy, we demonstrated that long-term oral administration of both cyclosporine and sirolimus at doses equivalent to the therapeutic levels used for postrenal transplant patients significantly affects testicular development and the hypothalamic-pituitary-gonadal axis accompanied by profound histological changes of testicular structures on both light and electron microscopic examinations. Spermatogenesis was also severely impaired as indicated by low total sperm counts along with reduction of sperm motility and increase in sperm abnormality after treatment with these agents, which may lead to male infertility. On the other hand, treatment with therapeutic dose of tacrolimus only induced mild reduction of sperm count without histological evidence of testicular injury. The current study clearly demonstrates that commonly used immunosuppressants have various impacts on male reproductive system even at therapeutic levels. Our data provide useful information for the assessment of male infertility in renal transplant recipients who wish to father children. Clinical trials to address these issues should be urged.